The Association of Vascular Loops within the Internal Auditory Meatus or Contacting the Vestibulo-Cochlear Nerve with Audiovestibular Symptoms: A Systematic Review and Meta-Analysis - Cowen, Jake E.; Tehrani, Mehrshad Sultani; Connor, Steve E.J. (American Journal of Neuroradiology, 2025)
BACKGROUND: Intrameatal vascular loops (IVL) entering the internal auditory meatus and neurovascular contact (NVC) with the vestibulocochlear nerve (cranial nerve [CN] VIII) have been proposed to have a relationship with audiovestibular symptoms.PURPOSE: This systematic review and meta-analysis aimed to determine whether the presence of IVLs and CN VIII NVC on MRI is associated with tinnitus, sensorineural hearing loss (SNHL), or vertigo and any specific subtypes.DATA SOURCES: All studies comparing the presence of IVL or CN VIII NVC in ears with these audiovestibular symptoms and controls were identified through MEDLINE, EMBASE, the Web of Science Core Collection, Scopus, and the Cochrane Register of Controlled Trials databases.STUDY SELECTION: Sixteen studies and 3455 ears (1526 symptomatic ears and 1929 control ears) were included.DATA ANALYSIS: Meta-analysis was performed using a bivariate random effects model. Pooled ORs were calculated, and heterogeneity was evaluated with the Cochran Q test with statistical significance defined as P < .05.DATA SYNTHESIS: There was no significant association between the presence of undefined tinnitus or SNHL and IVL (OR, 0.90; 95% CI, 0.47–1.70; OR, 0.67; 95% CI, 0.36–1.25) or CN VIII NVC (OR, 1.15; 95% CI, 0.68–1.95; OR, 0.89; 95% CI, 0.33–2.40). However, the subgroup of sudden onset SNHL was associated with IVL (OR, 1.34; 95% CI, 1.04–1.73) (P = .02). There was no significant difference in the prevalence of IVL (OR, 0.97; 95% CI 0.64–1.48) or CN VIII NVC (OR, 0.99; 95% CI, 0.42–2.32) between ears with undefined vertigo and control ears. However, there was an association between the presence of CN VIII NVC and the specific diagnosis of vestibular paroxysmia (OR, 13.19; 95% CI, 2.09–83.16) (P = .006).LIMITATIONS: Our meta-analysis is limited by selection bias, the small number of eligible studies, and moderate heterogeneity.CONCLUSIONS: IVL or CN VIII NVC on MRI is unrelated to symptoms of undefined tinnitus, SNHL, and vertigo. However, CN VIII NVC is associated with vestibular paroxysmia, while IVL is associated with sudden onset SNHL.CNcranial nerveIAMinternal auditory meatusIVLintrameatal vascular loopNVCneurovascular contactSNHLsensorineural hearing lossSoSNHLsudden onset sensorineural hearing loss